The "Rough Stones" of Aegina: Pindar, Pausanias, and the Topography of Aeginetan Justice. - KURKE, LESLIE (Classical Antiquity, 2017)
This paper considers Pindar's diverse appropriations of elements of the sacred topography of Aegina for different purposes in epinikia composed for Aeginetan victors. It focuses on poems likely performed in the vicinity of the Aiakeion for their different mobilizations of a monument that we know from Pausanias stood beside the Aiakeion--the tomb of Phokos, an earth mound topped with the "rough stone" that killed him (N.5, N.8, O.8). The more speculative final part of the paper suggests that it may also be possible to track a coherent ideology attached to the island's sacred topography across several Aeginetan odes, thereby detecting a broader structural unity that accompanies and frames the different individual appropriations of different poems. This part starts from Pausanias' mythic narrative of the exemplary justice of Aiakos banishing his own son Telamon as the aetiology for a distinctive Aeginetan justice system inscribed in a whole set of man-made monuments that ring the island with concentric circles of rough stones.